GREENHOUSE GAS EMISSIONS FROM CONSTRUCTED WETLANDS FOR ANAEROBIC SLUDGE TREATMENT: EFFECT OF SEASONALITY, PLANT SPECIES TYPE, AND SLUDGE LOADING - A PRELIMINARY ANALYSIS - Diogo A. P. da Silva; Mateus P. Matos; José Antônio Ribeiro de Araújo; Thiago de A. Neves (Química Nova)
At sewage treatment plants, sludge management remains a bottleneck, requiring efficient and cost-effective solutions for treating this solid byproduct. It is known that the presence of plants can accelerate the sludge drying process, as a result, vertically flowed constructed wetlands (VFCWs) have been evaluated as alternatives to traditional drying beds. Though, for better applicability of this technology, this study premised on evaluating greenhouse gas (GHG) emissions in VFCWs constructed for anaerobic sludge treatment. To compare GHG emissions across different seasonal conditions, three configurations were tested: four units planted with Tifton-85 grass (Cynodon spp.), four units planted with elephant grass (Cenchrus purpureus), four control units without vegetation presence, with four sludge loading rates in each configuration: 75, 100, 150, and 200 kg TS (total solids) m-2 year-1. Higher sludge loading rates led to increased methane emissions, with emissions escalating during the rainy season. Methane emissions decreased towards the end of the resting period. The presence of vegetation reduced methane emissions mainly during the resting period due to increased aeration of the units. The conditions that would provide lower GHG emissions would be with loads of up to 100 kg m-2 year-1, in units planted with Tifton grass.